2021
DOI: 10.3390/ijms22168576
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early Life Exposure to Cannabis: The Role of the Endocannabinoid System

Abstract: Cannabis use during pregnancy has continued to rise, particularly in developed countries, as a result of the trend towards legalization and lack of consistent, evidence-based knowledge on the matter. While there is conflicting data regarding whether cannabis use during pregnancy leads to adverse outcomes such as stillbirth, preterm birth, low birthweight, or increased admission to neonatal intensive care units, investigations into long-term effects on the offspring’s health are limited. Historically, studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 227 publications
(314 reference statements)
1
8
0
1
Order By: Relevance
“…No language restriction was applied. The search was restricted to studies published after 2000, because of the increase in THC potency in the last decades 22 . The mesh terms "marijuana use", "marijuana abuse", "cannabis" and "cannabinoids" were 5…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…No language restriction was applied. The search was restricted to studies published after 2000, because of the increase in THC potency in the last decades 22 . The mesh terms "marijuana use", "marijuana abuse", "cannabis" and "cannabinoids" were 5…”
Section: Search Strategymentioning
confidence: 99%
“…The search was restricted to studies published after 2000 because of the increase in THC potency in the last decades. 22 The mesh terms "marijuana use", "marijuana abuse", "cannabis," and "cannabinoids" were used to define the search expression, being adapted according to the different datasets. The search was followed by reference tracking, examining the references of the selected publications based on full-text assessment.…”
Section: Search Strategymentioning
confidence: 99%
“…The first ones isolated in 1975 (examples: dehydrocannabifuran DCBF-C5, cannabifuran CBF-C5) [23] The discovery of these compounds led to the identification of cannabinoid receptors (CB1 and CB2) and endogenous ligands of the endocannabinoid system. There is evidence that this system plays an essential role in many normal physiological processes, such as memory, cognition, learning, motor control, anxiety, appetite, sleep, lipogenesis, fertility, formation of insulin and muscle fibers, vasomotricity, intestinal and bronchial motility, and immune modulation, but also in pathological-like pain, inflammation, and cancer [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: The Number Of Compounds In Each Classmentioning
confidence: 99%
“…In addition to the physical health effects, preclinical studies have shown severe brain developmental consequences associated with prenatal synthetic cannabinoid exposure in chickens (Psychoyos, Hungund, Cooper, & Finnell, 2008), mice (Gilbert et al, 2016) and rats (Mereu et al, 2003). While examining later life behavior, prenatal cannabis use has also been found to have long-term effects on diminished verbal and memory skills (Day et al, 1994), increased impulsivity and hyperactivity (Richardson, Ryan, Willford, Day, & Goldschmidt, 2002) and decreased attention and concentration during childhood and adolescence (Fried & Smith, 2001; Martínez-Peña et al, 2021). Consequences of use also affect adult functioning including substance use, memory deficits and cognition, motivation and behavioral regulation (De Genna, Willford, & Richardson, 2022; Zamberletti & Rubino, 2022), as well as altered neural functioning during visuospatial working memory (Smith, Fried, Hogan, & Cameron, 2006).…”
Section: Introductionmentioning
confidence: 99%